2017
DOI: 10.1111/anu.12549
|View full text |Cite
|
Sign up to set email alerts
|

Dietary manganese requirement of juvenile hybrid grouper, Epinephelus lanceolatus  × E. fuscoguttatus

Abstract: An 8‐week feeding trial was conducted to estimate the optimum dietary manganese (Mn) requirement for juvenile hybrid grouper, Epinephelus lanceolatus × E. fuscoguttatus. The basal diet was formulated to contain 520 g/kg crude protein from casein and fishmeal. Manganese methionine was added to the basal diet at 0 (control group), 2.5, 5, 10, 20 and 40 mg Mn/kg diet providing 7.48, 10.34, 13.76, 19.72, 31.00 and 53.91 mg Mn/kg diet, respectively. Each diet was randomly fed to triplicate groups of juveniles, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…However, it was observed that Mn concentrations in several tissues of tilapia significantly increased with either Glu‐Zn or Nano ZnO diet when compared to ZnSO 4 diet, suggesting that Nano Zn and Glu‐Zn played a positive role in Mn accumulation in fish tissues. In previous studies, Zn and Mn interactions have been observed in gilthead seabream and cobia ( Rachycentron canadum ) (Domínguez et al, 2019; Nie et al, 2016), while the Zn was reduced with increasing dietary Mn in some fishes (Liu et al, 2018). However, there are also experiments reported that dietary Nano ZnO supplementation increased total body Mn concentration of marine medaka as compared to inorganic Zn (Jian Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…However, it was observed that Mn concentrations in several tissues of tilapia significantly increased with either Glu‐Zn or Nano ZnO diet when compared to ZnSO 4 diet, suggesting that Nano Zn and Glu‐Zn played a positive role in Mn accumulation in fish tissues. In previous studies, Zn and Mn interactions have been observed in gilthead seabream and cobia ( Rachycentron canadum ) (Domínguez et al, 2019; Nie et al, 2016), while the Zn was reduced with increasing dietary Mn in some fishes (Liu et al, 2018). However, there are also experiments reported that dietary Nano ZnO supplementation increased total body Mn concentration of marine medaka as compared to inorganic Zn (Jian Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…The pearl gentian grouper Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂ is a typical marine carnivorous fish, with fast growth rate, high market value, and high disease resistance. It is widely farmed in China and all over the world (Liu et al, 2018 ). Our previous research showed that high substitution levels of soy meal, such as SBM and FSBM, induced enteritis in the pearl gentian grouper.…”
Section: Introductionmentioning
confidence: 99%
“…According to the methods of Zhai et al (2016), the activities of amylase, lipase and protease in the intestine were analyzed by UV-Vis spectrophotometer (UV-1200, Shanghai Mipoda Instrument Co., Ltd., China). The malondialdehyde (MDA) level, total antioxidant capacity (T-AOC) activity, superoxide dismutase (SOD) activity, catalase (CAT) activity, and glutathione peroxidase (GSH-Px) activity were tested by Multifunctional Microplate Reader (TECAN Infinite 200 PRO, Tecan Austria GmbH, Austria) with commercial kits according to the descriptions of Zhai et al (2016;2018). The level of MDA was expressed as nmol/mg protein.…”
Section: Sample Collection and Analysismentioning
confidence: 99%
“…The pearl gentian grouper (Epinephelus fuscoguttatus female x Epinephelus lanceolatus male), a marine carnivorous fish species, has the advantages of fast growth, high market value, and strong disease resistance. It is a new candidate which is widely cultured in China and over the world (Liu et al, 2018). This study aimed to evaluate the effects of GSPs on alleviating dietary Cd-induced growth retardation and damages of intestinal health parameters in pearl gentian grouper.…”
Section: Introductionmentioning
confidence: 99%